The comunication climate: the individual and shared perceptions of polices and practices in organizational comunication: La percepción individual y compartida de las políticas y prácticas de comunicación organizacional - Hernández García, David (Folios, revista de la Facultad de Comunicaciones y Filología, 2012)
The organizational comunication climate has had a broad ressearch devekopment in recent years. From this perspective, this paper introduces sveral scopes used by comunication and psychology scholars on the origins and consecuences, both individul and organizational, the cognitive snd effective perceptions contucted by employees about the organizatio, and in particular, their comunicaction caracteristics.